The Evolution of Neuroinclusion: Historical and Semantic Perspectives in European Education - Shelever, O.; Ribtsun, Y.; Shevchenko, V.; Shevchenko, S.; Soichuk, R.; Kuzava, I. (Revista Romaneasca Pentru Educatie Multidimensionala, 2025)
The article explores the concept of inclusion within European pedagogy, with particular attention to its integration into the neuropsychological context. It examines the historical evolution of inclusive education, key conceptual shifts, and the current challenges that educators face. Emphasis is placed on the notion of neuroinclusion – a new approach aimed at integrating neurodivergent students into mainstream educational settings. This article addresses the timely and underexplored phenomenon of neuroinclusion in European pedagogy. It offers a detailed analysis of the concept’s evolution, its theoretical underpinnings, and its practical application in the educational process. Neuroinclusion, which merges insights from neuroscience with the principles of inclusive education, is gaining increasing relevance in today’s education. By understanding the neurobiological foundations of learning and development, educators can create more individualized and effective learning environments. The article traces the historical development of the neuroinclusion concept. It outlines its core ideas and foundational approaches. It also examines the current state of neuroinclusive practices in various European countries. Additionally, it discusses the main challenges and prospects related to implementing neuroinclusion in education.
Keywords: Neuroinclusion; inclusive education; European pedagogy; neuropsychology; adaptation; cognitive features